PENGEMBANGAN E-MODUL TERINTEGRASI QR CODE MATERI KEBERAGAMAN BUDAYA BANGSAKU KELAS IV SDN 14 MENDO BARAT - Hikmatul Uzma; Nurjannah; Feni Kurnia (JBES (Journal Basic Education Skills), 2025)
This research was motivated by the limitations of the media used in the learning process, causing a lack of student response, which affected student learning outcomes. The aim of this research is 1) to produce an integrated e-module QR Code teaching material product on the cultural diversity of my nation for grade 4 elementary schools that is feasible and practical, and 2) to determine the effectiveness of the e-module integrated with QR Code material on the cultural diversity of my nation for grade 4 elementary schools that was developed. This type of research is R&D (research and development) based on the ADDIE (analysis, design, development, implementation, and evaluation) model. This study was conducted with fourth graders at SD Negeri 14 Mendo Barat. Data collection techniques include tests and non-tests. Data collection instruments include questionnaires, interviews, and 10 test questions. To test effectiveness, the data analysis techniques used are descriptive qualitative, normality testing, and hypothesis testing using the paired samples t-test. Based on the assessment results, material validators received an average of 92.3%, and media validators received an average of 82%. Small-group trials had 100% results, whereas large-group trials had 100%. Class IV student responses to the questionnaire were 100%. The results of the paired sample t-test (t-count > t-table) are 10.825> 2.068. Thus, Ha is accepted, meaning that there is effectiveness in using the E-Module in the Cultural Diversity of My Nation class IV material at SD Negeri 14 Mendo Barat. It can be concluded that the e-module, combined with QR Code material on cultural diversity in my country, is feasible, practical, and effective for use as teaching material.